ADDRESSING GLOBAL ENERGY AND SECURITY CHALLENGES - LINOTTE, Daniel; REUCHLIN, Philip (CENTRAL ASIA AND THE CAUCASUS, 2005)
The geographical distribution of current energy resources is quite uneven which makes some countries and regions major suppliers of energy products, oil and gas in particular. Key-suppliers of energy products are located in the Middle East, the CIS, Africa and Latin America whereas North America, Europe, and South and East Asia are major consumers. Recent events show that energy prices can change rapidly, reacting to economic, social and political events in oil exporting countries. Energy policies and strategies may trigger tensions between countries. Moreover, there are growing concerns about the safety of energy transportation routes and security in transit countries. In addition, extraction, transportation, storage, processing and final uses of energy resources do impact on the environment in many negative ways.These basic facts and the development of energy security concepts and strategies in some countries underline the importance of energy security issues and the need to assess linkages be-tween energy and security systematically.In that context, international and region-al cooperation, organizations and treaties are key-components of energy security and subsequently, a strengthening and better use of existing institutional frameworks should be advocated.